Application of Fuzzy Simple Additive Weighting Method in Group Decision-Making for Capital Investment - Aliyeva, Kamala; Aliyeva, Aida; Aliyev, Rashad; Ozdeser, Mustafa (Mdpi, 2023)
Investment management is a common process and practice used for achieving a desirable investment goal or outcome. Unfortunately, the systematic variation of economic situations in the marketplace effects the continuous and frequent change of investment conditions and environment in which the investor should act and operate. Hence, the rules required for providing a reasonable quality of investment projects can be based only on the investor's management strategy, intuition and practice. There exists various decision-making approaches to investment management, and simple additive weighting (SAW) is one of the most well-known multicriteria decision-making (MCDM) methods aiming to provide an optimal decision for the decision-maker when solving various real-life problems, particularly investment problems. In this paper, the fuzzy simple additive weighting (FSAW) method is applied in group decision-making to undertake capital investment expenditure for purchasing cars with the purpose of renting them out to the public. A numerical example illustrates the importance and effectiveness of the suggested approach with the aim of ranking alternatives, and, hence, determining the preferred alternative in the MCDM problem.
Keywords: investment management; multi-criteria decision-making (MCDM); fuzzy number; fuzzy simple additive weighting; fuzzy group decision-making